2004
DOI: 10.1124/jpet.104.076406
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor mGlu5 Is a Mediator of Appetite and Energy Balance in Rats and Mice

Abstract: The metabotropic glutamate receptor subtype mGlu5 modulates central reward pathways. Many transmitter systems within reward pathways affect feeding. We examined the potential role of mGlu5 in body weight regulation using genetic and pharmacological approaches. Adult mice lacking mGlu5, mGluR5 Ϫ/Ϫ , weighed significantly less than littermate controls (mGluR5 ϩ/ϩ ), despite no difference in ad libitum food intake. After overnight food deprivation, mGluR5Ϫ/Ϫ mice ate significantly less than their mGluR5 ϩ/ϩ contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…On the other hand, administration of glutamate agonists directly into the lateral hypothalamus induces binge-type eating in rats, and this effect is blocked by the administration of NMDA receptor antagonists (Khan et al 2004). Peripheral administration of the mGlu5 antagonists MPEP or MTEP reduced food intake in rodents (Bradbury et al 2005;Semenova and Markou 2007), and food BP in rats (Paterson and Markou 2005). And, finally, NMDA receptor antagonists also suppress feeding induced by food deprivation (Stanley et al 1996) and by the infusion of neuropeptide Y (Lee and Stanley 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, administration of glutamate agonists directly into the lateral hypothalamus induces binge-type eating in rats, and this effect is blocked by the administration of NMDA receptor antagonists (Khan et al 2004). Peripheral administration of the mGlu5 antagonists MPEP or MTEP reduced food intake in rodents (Bradbury et al 2005;Semenova and Markou 2007), and food BP in rats (Paterson and Markou 2005). And, finally, NMDA receptor antagonists also suppress feeding induced by food deprivation (Stanley et al 1996) and by the infusion of neuropeptide Y (Lee and Stanley 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Metabotropic glutamate receptors include eight subtypes that have been divided into three groups according to G-protein coupling and sequence homology: group I (mGluR1, 5), group II (mGluR2-3), and group III (mGluR4, 6-8;Conn and Pin, 1997). The moderate to high density localization of mGlu5 receptors in the frontal cortex, striatum, nucleus accumbens, and hippocampus , as well as their modulatory role in membrane excitability in these regions (eg Domenici et al, 2003) has made them a target of interest for pharmacotherapeutic intervention in substance dependence (Chiamulera et al, 2001) and obesity (Bradbury et al, 2005). Noncompetitive antagonists of mGluR5 decrease selfadministration of cocaine (Kenny et al, 2005), ethanol (Cowen et al, 2005), and nicotine (Paterson and Markou, 2005;Paterson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that metabotropic glutamate receptor activation exerts strong excitatory effects on MCH and hypocretin neurons in the LH, suggesting these receptors may be involved in food intake and energy homeostasis. Supporting this view, mice lacking mGluR5 weigh less than their normal littermates and an mGluR5 antagonist MPEP decreases fasting-induced refeeding in wild but in not mGluR knock-out mice (Bradbury et al, 2005). mGluRs may interact with signals related to energy homeostasis.…”
Section: Relevance To Mch Neuron Role In Energy Homeostasismentioning
confidence: 94%
“…Functional experiments demonstrate that mGluR5 modulates food intake and energy balance (Bradbury et al, 2005). Group III mGluRs inhibit LH neurons .…”
Section: Introductionmentioning
confidence: 99%